Workshop Transformasi Kelas dengan Smart TV Digital: Optimalisasi TV Digital Pemerintah sebagai Jendela Dunia di Kelas - Ahmad, Ahmad; Aris Suziman; Waode Ekadayanti; Sri Marlia Puteri; Waode Heni Fitriani; Hesti Hesti; Ode Yahyu Herliani Yusuf (Prodi PGSD Unsultra, 2026)
The development of digital technology has driven the need for classroom transformation towards innovative, contextual learning, and oriented towards strengthening 21st-century competencies. One potential technology that can be utilized in elementary schools is government digital TV supported by Smart TV devices. However, the use of this technology has not been optimal due to the limited digital literacy of teachers. This community service activity aims to improve the digital literacy of teachers at SDN 8 Konda through the Classroom Transformation Workshop with Digital Smart TV: Optimizing Government Digital TV as a Window to the World in the Classroom. The implementation method uses a participatory approach that actively involves teachers through four stages: planning, workshop implementation, mentoring, and evaluation. The results of the activity show that the workshop and mentoring were able to improve teachers' understanding of digital literacy, government digital TV policies, and skills in operating and integrating Smart TV into learning. Teachers began to be able to design audiovisual-based learning that is more contextual, interactive, and relevant to the characteristics of students. In addition, this activity also increased teachers' confidence in utilizing technology as part of a pedagogical strategy. The evaluation of the activity showed a positive response from participants and increased awareness of the importance of digital literacy in supporting classroom transformation. Thus, optimizing the government's Smart TV-based digital TV program has proven effective as a means of strengthening teachers' digital literacy and has the potential to become a model for developing innovative learning in elementary schools.